NRG Oncology CC001 Neurocognitive Final Analysis: A Phase III Trial of Hippocampal Avoidance (HA) in Addition to Whole-Brain Radiotherapy (WBRT) Plus Memantine to Preserve Neurocognitive Function (NCF) in Patients With Brain Metastases (BM). (1st September 2019) - Wefel, Jeffrey S; Pugh, Stephanie; Gondi, Vinai; Brown, Paul D; Tome, Wolfgang; Armstrong, Terri S; Bruner, Deborah; Bovi, Joseph; Robinson, Cliff; Khuntia, Deepak; Grosshans, David; Konski, Andre; et al.
Abstract: INTRODUCTION: NRG CC001, a phase III trial of whole-brain brain radiotherapy (WBRT) plus memantine (WBRT + M) with or without hippocampal avoidance (HA), sought to evaluate the neuroprotective effects of lowering hippocampal radiation dose. METHODS: Patients with brain metastases (BM) were stratified by RPA class and prior radiosurgery/surgery and randomized to WBRT + M or HA-WBRT + M (30 Gy/10 fractions). Neurocognitive function (NCF) testing was performed at baseline, 2, 4, 6, and 12 mo. The primary endpoint was NCF failure, defined as reliable change index determined decline on Hopkins Verbal Learning Test-Revised, Trail Making Test, or Controlled Oral Word Association. Cumulative incidence estimated NCF failure (death without NCF failure was competing risk); between-arms differences tested using Gray's test. Deterioration at each time point was tested using a chi-square test. Patient-reported symptoms were assessed using the MD Anderson Symptom Inventory with Brain Tumor module (MDASI-BT) and analyzed using mixed effects models and t -tests. RESULTS: From 7/2015 to 3/2018, 518 patients were randomized. Median follow-up was 7.9 mo. HA-WBRT + M was associated with lower NCF failure risk (adjusted hazard ratio (HR) = 0.74, P = .02) due to lower risk of deterioration in executive function at 4 mo ( P = .01), and encoding ( P = .049) and consolidation ( P = .02) at 6 mo. Age = 61 predicted lower NCF failure risk (HR = 0.60, P = .0002); nonsignificant interaction test indicated independent effects of HA and age. On the patient-reported MDASI-BT, mixed effects models for Symptom Severity ( P = .03) showed a time-by-treatment interaction favoring HA-WBRT. Changes in the MDASI-BT Cognitive Factor at 6 mo ( P = .034) favored the HA-WBRT + M arm. The MDASI-BT items of problems remembering things ( P = .013), difficulty speaking ( P = .049), and fatigue ( P = .036) at 6 mo also favored the HA-WBRT + M arm. Treatment arms did not differ in toxicity, overall survival, or intracranial progression. CONCLUSION: HA during WBRT for BM better preserves NCF and patient-reported symptoms, while achieving similar intracranial control and survival.